Choice: Caribbean agriculture our way - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This publication addresses the many micro, small and medium entrepreneurs in the Caribbean, encouraging local and practical solutions to global challenges and adopting a proactive stance to improve the situation in agriculture and the economy.